1993
DOI: 10.1002/jmv.1890390213
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 and cytomegalovirus in saliva

Abstract: The aim of this study was to evaluate whether HIV-1 or cytomegalovirus (CMV) may contribute to oral lesions frequently found in patients with the acquired immunodeficiency syndrome (AIDS). Saliva samples from 63 HIV-1 positive patients and 21 healthy controls were tested for the presence of HIV-1 and CMV using the polymerase chain reaction (PCR) and virus isolation. CMV IgG titres in serum were also compared in the different groups. HIV-1 RNA, but not DNA, was detected in saliva from 15% (9 out of 59) of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…It is well known that CMV-associated lower frequency of HHV-8 DNA found in our study (5 [11%] of 44 patients) may be related to less-severe immunodeficiency diseases occur most frequently in patients with peripheralblood CD4 / cell counts of õ0.1 1 10 9 /L. It has been suggested and to the possibility that Kaposi's sarcoma is less frequent among HIV-1-infected homosexual men in Sweden [2] than in that the presence of CMV could be related to the oral ulcerations [10] seen in patients with AIDS. Such a relationship some other countries.…”
supporting
confidence: 45%
See 2 more Smart Citations
“…It is well known that CMV-associated lower frequency of HHV-8 DNA found in our study (5 [11%] of 44 patients) may be related to less-severe immunodeficiency diseases occur most frequently in patients with peripheralblood CD4 / cell counts of õ0.1 1 10 9 /L. It has been suggested and to the possibility that Kaposi's sarcoma is less frequent among HIV-1-infected homosexual men in Sweden [2] than in that the presence of CMV could be related to the oral ulcerations [10] seen in patients with AIDS. Such a relationship some other countries.…”
supporting
confidence: 45%
“…HHV-8 DNA. HHV-8 DNA was detected in patients in CDC K, was performed as described previously [2]. This method results in a 1:2 dilution of saliva.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The specialized secretory machinery of glandular epithelial cells is utilized by the virus for highly efficient virion production and excretion in saliva for long periods of time (13,17,27). While CMV infection can cause morbidity and mortality in neonates and immunocompromised individuals, infection of immunocompetent individuals is largely asymptomatic (40).…”
mentioning
confidence: 99%
“…In this study, no definite CMVdiseases were observed, although CMVDNA was detected 8 times in 4 patients repeatedly. The PCRtechnique for detection of CMVDNA,although it assures high sensitivity, risks the possibility of detection of latent CMV infection, thereby leading to false-positive results (19). It has been demonstrated that CMVDNAcould be detected with PCR during the initial stage of acute infection and before the onset of symptomsor identification of the infection by standard methods (7).…”
Section: Discussionmentioning
confidence: 99%